Variation of the Number of Heat Sources in Methane Dry Reforming: A Computational Fluid Dynamics Study - Sunggeun Lee; Hankwon Lim (International Journal of Chemical Engineering)
To overcome the weak point of the gas type heating (failure in heating uniformly and persistently), liquid type molten salt as a concentration of solar energy was considered as a heat source for dry reforming. This high-temperature molten salt flowing through the center of the tubular reactor supplies necessary heat. The dependence on the number of heat source of the hydrogen production was investigated under the assumption of the fixed volume of the catalyst bed. By changing these numbers, we numerically investigated the methane conversion and hydrogen flow rate to find the best performance. The results showed that the methane conversion performance and hydrogen flow rate improved in proportion to the number of heating tubes. For the one heat source, the reactor surrounded by a heat source rather than that located in the center is the best in terms of hydrogen yield. In addition, this study considered the case in which the system is divided into several smaller reactors of equal sizes and a constant amount of catalyst. In these reactors, we saw that the methane conversion and hydrogen flow rate were reduced. The results indicate that the installation of as many heating tubes as possible is preferable.